Photoreceptor-induced LHL4 protects the photosystem II monomer in Chlamydomonas reinhardtii - Marie Dannay; Chloé Bertin; Eva Cavallari; Pascal Albanese; Dimitri Tolleter; Cécile Giustini; Mathilde Menneteau; Sabine Brugière; Yohann Couté; Giovanni Finazzi; Emilie Demarsy; Roman Ulm; et al. (Proceedings of the National Academy of Sciences, 2025)
Photosynthesis, the fundamental process using light energy to convert carbon dioxide to organic matter, is vital for life on Earth. It relies on capturing light through light-harvesting complexes (LHC) in photosystem I (PSI) and PSII and on the conversion of light energy into chemical energy. Composition and organization of PSI and PSII core complexes are well conserved across evolution. PSII is particularly sensitive to photodamage but benefits from a large diversity of photoprotective mechanisms, finely tuned to handle the dynamic and ever-changing light conditions. Light Harvesting Complex protein family members (LHC and LHC-like families) have acquired a dual function during evolution. Members of the LHC antenna complexes of PS capture light energy, whereas others dissipate excess energy that cannot be harnessed for photosynthesis. This process mainly occurs through nonphotochemical quenching (NPQ). In this work, we focus on the Light Harvesting complex-Like 4 (LHL4) protein, a LHC-like protein induced by ultraviolet-B (UV-B) and blue light through UV Resistance locus 8 (UVR8) and phototropin photoreceptor-activated signaling pathways in the model green microalgae Chlamydomonas reinhardtii . We demonstrate that alongside established NPQ effectors, LHL4 plays a key role in photoprotection, preventing singlet oxygen accumulation in PSII and promoting cell survival upon light stress. LHL4 protective function is distinct from that of NPQ-related proteins, as LHL4 specifically and uniquely binds to the transient monomeric form of the core PSII complex, safeguarding its integrity. LHL4 characterization expands our understanding of the interplay between light harvesting and photoprotection mechanisms upon light stress in photosynthetic microalgae.